Judicial control over the decisions of separation of heads of administrative units in Iraq - عبد الرزاق عبدالرسول قحطان; قدوري تغريد محمد (Journal of Legal Sciences, 2021)
Legislation under study organized the judicial control over the decisions of the end of service heads of administrative units in Iraq, since before the first amendment to the law of the governorates in the irregular province No. (21) for the year 2008 was the appeal before the Federal Supreme Court and after the first amendment became the decision to dismiss the governor and the governor The Governing Law stipulates that the Governor may appeal against his dismissal before the Administrative Judicial Court within fifteen days from the date of his notification. The law obliges the court to rule on the judgment with in (30) days The law did not provide for the governorates in force to appeal the dismissal decision، and the law did not provide for the legal periods for the appeal of the governor in relation to the appeal against the decision to dismiss the Qaimqam and the director of the district, as reference to the provisions of the Law of the Iraqi Council of State No. (71) of 2017 in force for legal periods and grievance..